Selection and Success in Badminton: The Role of Lobs and Smashes in Junior Athletes' Performance - Touptiolo, Touptiolo; Siregar, Helmina Ria; Tarigan , Vina Mardatila; Suwananda , Yogi; Hattabi, Soukaina; Nance, Willette (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. This study examines the effectiveness and tactical implications of lob and smash strategies in competitive badminton among junior athletes. Materials and methods. Through quantitative analysis of 32 junior players (16 males, 16 females, aged 14-18 years), we investigated shot frequency, success rates, and contextual factors influencing strategy selection. Results. Results indicate that lobs constituted 18.3% (±3.2%) of total shots with a 62.1% (±5.7%) success rate, while smashes accounted for 12.7% (±2.8%) of shots with a 71.4% (±6.3%) success rate. Logistic regression analysis revealed that court position, rally length, and score difference significantly influenced shot selection (p < 0.001). Smashes were predominantly used from the forecourt (OR = 3.842, p < 0.001), while lobs were more frequent in longer rallies (OR = 1.180 per additional shot, p < 0.001). Gender differences were observed, with female players using lobs more frequently than males (19.5% ±3.0% vs. 17.1% ±3.4%, p = 0.037). Two-way ANOVA revealed a significant interaction between shot type and rally length on success rate (F(3, 124) = 7.936, p < 0.001, partial η² = 0.161). Conclusions. These findings provide insights into optimal shot selection and its impact on game outcomes among junior badminton players. The study contributes to the development of effective training programs and tactical approaches, emphasizing the importance of contextual factors in strategic decision-making. Future research directions include longitudinal studies of tactical development and investigation of these strategies in doubles play.